Addressing Loneliness: A Variety of Approaches - Rokach, Ami (Ruch Filozoficzny, 2024)
Loneliness has been with us since the beginning of time. Many ask themselves what can they do about loneliness? It is impossible, of course, to eradicate it. It is simply part of being human, just like hunger and physical pain. We can, though, address its pain and possibly lower its frequency in our lives. This article reviews the field of treatment of the pain caused by loneliness, and assisting people, of various ages, reduce its frequency. The appointment of a minister of loneliness in the UK, may be a right step in getting loneliness out of the “closet”, and in the forefront of public awareness and the state’s attempts to address it on a national level.